Menulis Teks Eksplanasi Menggunakan Metode Quantum Learning di SDN Sindangrasa Kota Bogor - Siti Solihah; Deasy Supartini (Universitas Maritim AMNI Semarang, 2022)
The purpose of this study was to determine the students ‘ writing ability in explanatory texts using the quantum learning method in fifth grade elementary school students. Sindangrasa Bogor City. This research will be carried out through 2 cycles. Each cycle consists of planning, implementation, observation and reflection. This technique uses data collection and observation through demontrations, and texts. The result of the first cycle is getting an average score of 37,60 or 60 % . Then the second cycle greatly improved by obtaining an average score of 48,90 or 85 % of the data in the first and second cycles showing an increase in student learning in writing explanatory texts. Student learning oucomes in the first cycle was 65,42 while the learning outcomes from the second cycle were 82,86 . So all student meet the increase and meet the KKM value. Student data obtained from cyclesI and II show an increase with the avarage score of student activity which is quite significant.